MHD Flow of Jeffery Nanofluid Through Symmetric Ciliated Channel with Porous Medium: Biological Application - Ali, Hayat A.; Abdulhadi, Ahmed M.; Kashem, Bushra. E. (Iraqi Journal of Science, 2024)
This paper emphasizes on examining the impact of a magnetic field, and porous medium on the non-Newtonian Jeffery nanofluid flows due to metachronal waves induced by ciliated structures that covering the inner walls of the symmetric channel. The governing equations namely continuity, motion, energy and nanoparticles concentration are formulated with suitable boundary conditions and simplified depending on the assumption of long wavelength and low Reynolds number. The simplified equations are solved by using Mathematica program. Further, these analytical solutions for velocity profile, temperature, concentration profiles and streamlines are graphically elucidated and discussed in detail. we concluded that the Hartman number and permeability parameter have opposite effect on the flow characteristics. Moreover, the Jeffery parameter  has an increasing impact on the velocity profile whereas the dimensionless eccentricity of ellipse parameter  decreases the velocity profile of the fluid.